Navigating complexities in on-the-job training at vocational institutions: a systematic literature review - Rajamanickam, Selvi; Che Rus, Ridzwan; Abdul Raji, Mohd Nazri (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study aims to systematically review and analyze the integration of fourth industrial revolution (IR 4.0) technologies into technical and vocational education and training (TVET) through on-the-job training (OJT), focusing on key themes such as skills development in the digital age, workforce productivity, relevance of IR 4.0 technologies, and the role of OJT in TVET. Additionally, it seeks to identify the challenges and best practices associated with this integration, offering actionable insights for policymakers, educators, and industry stakeholders to enhance skills development and workforce adaptability in the context of the IR 4.0. A systematic literature review was conducted to understand the multifaceted challenges and opportunities surrounding OJT programs within TVET institutions. Given TVET’s vital role in equipping individuals with workforce-relevant skills, optimizing OJT programs is crucial for meeting modern industry demands. The PRISMA framework guided the review, using advanced search techniques on databases such as Scopus, ERIC, and IEEE, leading to the analysis of 35 primary sources. The review addressed areas including the adaptation of training to modern technologies, labor market outcomes, innovative practices for competency development, and ensuring equity and access in vocational training. It identified best practices, highlighted knowledge gaps, and provided recommendations to optimize OJT in TVET. Key findings emphasized aligning OJT with emerging technologies, enhancing employment outcomes, promoting innovative training methods, and ensuring inclusive and effective vocational training. The study concludes by offering recommendations to improve the quality and outcomes of OJT in TVET, ensuring alignment with evolving workforce and industry needs.